Fibrinolytic System in Patients with Hypertensive Cardiovascular Disease - Prokopowicz, J; Worowski, K; Popławski, A; Gabryelewicz, A; Niewiarowski, S (Thrombosis and Haemostasis, 1967)
The fibrinolytic system has been studied in 37 patients with essential hypertension, with arterial hypertension of various etiology (renal hypertension and hypertension with atherosclerosis). It has been found that in all these patients euglobulin fibrinolysis is inhibited and fibrinogen, factor VIII, plasminogen, plasminogen proactivator and antiplasmin increase considerably.On the basis of the above findings and other literature data, the authors present a hypothesis that the fibrinolytic system is involved in the regulation of arterial blood pressure and that the impairment of plasminogen activator production in the renal tissue is one of the contributory factors in the development of arterial hypertension.